Alkaline Phosphatase Activity of Marsilea crenata Presl. Extract and Fractions as Marker of MC3T3-E1 Osteoblast Cell Differentiation - Burhan Ma’arif, Mangestuti Agil, Hening Laswati (Journal of Applied Pharmaceutical Science, 2018)
Phytoestrogen is a group compound which has estrogen-like structure or function. The aim of this research was to evaluate phytoestrogen stimulating activity inside Marsilea crenata Presl leaves on alkaline phosphatase (ALP), a marker in osteoblast differentiation. Osteoblast cells were exposed with n-hexane extract of M. crenata leaves with dose 400, 200, 100, 50, and 25 ppm, and 4 fractions of M. crenata leaves with dose 25 ppm for 48 hours. N-hexane extract and four fractions of M. crenata leaves were tested using immunocytochemistry (ICC) and confocal laser scanning microscopy (CLSM). The results showed anon monotonic response was between dose improvement of n-hexane extract and ALP activity, whereas fraction 2 and fraction 4 were able to increase ALP activity that valued of 96.711 and 131.840, respectively, which was more than control. Through correlation analysis between research result and literature, it could be concluded that palmitic acid in fraction 2 and fraction 4 were phytoestrogen compound in M. crenata that played role in the improvement of ALP activity in MC3T3-E1 osteoblast cell.
Keywords: Marsilea crenata Presl., MC3T3-E1, alkaline phosphatase, phytoestrogens.